Green Tea (Camellia sinensis) Extract Increased Topoisomerase IIβ, Improved Antioxidant Defense, and Attenuated Cardiac Remodeling in an Acute Doxorubicin Toxicity Model. (5th May 2021) - Modesto, Pamela N.; Polegato, Bertha F.; dos Santos, Priscila P.; Grassi, Leticia D. V.; Molina, Leticia C. C.; Bazan, Silmeia G. Z.; Pereira, Elenize J.; Fernandes, Ana Angelica H.; Fabro, Alexandre T.; Androcioli, Vickeline N.; Roscani, Meliza G.; de Paiva, Sergio A. R.; et al.
Abstract : Experimental studies have shown the action of green tea in modulating cardiac remodeling. However, the effects of green tea on the cardiac remodeling process induced by doxorubicin (DOX) are not known. Therefore, this study is aimed at evaluating whether green tea extract could attenuate DOX-induced cardiac remodeling, assessed by cardiac morphological and functional changes and associated with the evaluation of different modulators of cardiac remodeling. The animals were divided into four groups: the control group (C), the green tea group (GT), the DOX group (D), and the DOX and green tea group (DGT). Groups C and GT received intraperitoneal sterile saline injections, D and DGT received intraperitoneal injections of DOX, and GT and DGT were fed chow supplemented with green tea extract for 35 days prior to DOX injection. After forty-eight hours, we performed an echocardiogram and euthanasia and collected the materials for analysis. Green tea attenuated DOX-induced cardiotoxicity by increasing cardiac function and decreasing the concentric remodeling. Treatment with DOX increased oxidative stress in the heart, marked by a higher level of lipid hydroperoxide (LH) and lower levels of antioxidant enzymes. Treatment with green tea increased the antioxidant enzymes' activity and decreased the production of LH. Green tea extract increased the expression of Top2- β independent of DOX treatment. The activity of ATP synthase, citrate synthase, and complexes I and II decreased with DOX, without the effects of green tea. Both groups that received DOX presented with a lower ratio of P-akt/T-akt and a higher expression of CD45, TNF α, and intermediate MMP-2, without the effects of green tea. In conclusion, green tea attenuated cardiac remodeling induced by DOX and was associated with increasing the expression of Top2- β and lowering oxidative stress. However, energy metabolism and inflammation probably do not receive the benefits induced by green tea in this model.